Income inequality in the northern states of Malaysia: an analysis of income quintile - Mohd, Saidatulakmal; Senadjki, Abdelhak; Hamat, Abdul Fatah Che; Bahari, Zakaria (2015)

(untitled)
Between 1990 and 2010, income inequality in developing countries rose 11 percent. Inequality is perceived as a considerable threat to human development because it reflects unbalanced economic opportunities and affect individual’s well-being. The 2014 UNHDR indicates that twothirds of the world’s population are estimated to receive less than 13 percent of world income, while the richest 1 percent received nearly 15 percent of world income. In the Malaysian scenario the income inequality has improved only marginally. In 17 years from 1992 to 2009, the ratio of the mean income of the top 20 percent to the bottom 40 percent has improved slightly from 7.4 percent to 6.9 percent. Income inequality in Malaysia can be accessed using two measures; the income quintile (top 20 per cent, middle 40 per cent and bottom 40 per cent) and Gini Coefficient. While both measures are computed and updated regularly by EPU (Economic Planning Unit) for the whole country, the same are not done for individual states in Malaysia. The objective of this paper is to examine income inequality in the Northern States by using income quintile approach. Income quintiles are divided into three categories: top 20 percent, middle 40 percent, and bottom 40 percent. The 2009 household income survey reveals that the mean income of the top 20 percent, middle 40 percent, and bottom 40 percent are, RM 7,639, RM 2,862, and RM 1,206 respectively. A big proportion of the Northern States income is concentrated among the top 20 percent of the population. To further understand the situation, analysis by states, strata, and ethnicity is carried out. An interesting finding to note is that Perlis, the poorest state among the group has the highest inequality because a big proportion of the income goes to the richest 20 percent of its population. Rural areas and Bumiputera remain the disadvantaged groups with low mean income.